Reform of Muslim personal law - Gani, H. A. (New Delhi, 1988)
Few issues pertaining to minorities have roused so much concern and debate among intellectuals as the one single issue of Reform of Muslim Personal Law. The controversy essen tially centres round the now famous Shahbano Case and the recently enacted Muslim Women (Protection of Rights on Divorce) Act, 1986. The author focuses his searchlight, not only on the Government's attitude but also on the views of the opposition and leading Muslims as well as Non-Muslim intellectuals. Dr. Gani attri butes the Government's reluctance to reform Muslim Personal Law to political considerations and opines that in the long run this reluctance could prove baneful to the community as well as the country.
Keywords: Islamic Law-India